Juridical Analysis of Legal Aspects of Adolescent Reproductive Health Services - C.Wibowo; E.Saputra (The Medical Journal of Hospital Management and Health Law, 2026)
Introduction: Adolescent reproductive health remains a critical socio-legal issue globally, particularly within developing legal frameworks where the protection of minor rights often intersects with parental authority and public morality. While healthcare policies emphasize accessibility, statutory ambiguities frequently restrict adolescents from independently obtaining reproductive health services. This study addresses this friction by evaluating how current legal systems balance protectionism with autonomy. Methods: This research employs a normative juridical method, utilizing a statutory and conceptual approach to analyze relevant laws, health regulations, and human rights conventions. Results: The findings reveal a significant legal disharmony between national health statutes that guarantee health access and specific medical regulations that condition reproductive interventions on marriage or parental consent. This inconsistency creates legal uncertainty for healthcare providers and effectively bars unmarried adolescents from crucial services. Discussion: The discussion integrates an extensive literature review, emphasizing that the legal framework fails to incorporate the principle of the evolving capacities of the child as mandated by international law. By enforcing rigid age thresholds and marital requirements, the law neglects the public health reality of adolescent sexual activity, thereby widening the research gap between statutory law and societal needs. Conclusions: In conclusion, the legal architecture governing adolescent reproductive health requires immediate harmonization to reconcile rights-based approaches with protective regulations. It is recommended that policymakers amend restrictive health regulations to establish clear, age-appropriate consent mechanisms, alongside developing comprehensive guidelines that shield medical practitioners from liability when serving adolescents.